Efficient Genome Editing in Setaria italica Using CRISPR/Cas9 and Base Editors - Liang, Zhen; Wu, Yuqing; Ma, Lingling; Guo, Yingjie; Ran, Yidong (Frontiers in Plant Science, 2022)
The genome editing toolbox based on CRISPR/Cas9 has brought revolutionary changes to agricultural and plant scientific research. With the development of stable genetic transformation protocols, a highly efficient genome editing system for foxtail millet (Setaria italica) is required. In the present study, we use the CRISPR/Cas9 single- and multi-gene knockout system to target the SiFMBP, SiDof4, SiBADH2, SiGBSS1, and SiIPK1 genes in the foxtail millet protoplasts to screen out highly efficient targeted sgRNAs. Then, we recovered homozygous mutant plants with most of the targeted genes through an Agrobacterium-mediated genetic transformation of foxtail millet. The mutagenesis frequency in the T0 generation was as high as 100%, and it was passed stably on to the next generation. After screening these targeted edited events, we did not detect off-target mutations at potential sites. Based on this system, we have achieved base editing successfully using two base editors (CBE and ABE) to target the SiALS and SiACC genes of foxtail millet, which resulted in a homozygous herbicide-resistant mutant plant. The current system could enhance the analysis of functional genomics and genetic improvement of foxtail millet.